Ender's Nail For Diaphyseal Long Bone Lower Limb Fractures in Children - Sohail Iqbal Sheikh, Muhammad Ullah, Arab Khan,Javed Iqbal (Journal of Rawalpindi Medical College, 2012)
Background: To assess the efficacy of flexible intramedullary Enders nails(EN) for the treatment of femoral and tibial diaphyseal fractures in children. Methods: In this descriptive study, thirty patients treated with EN, for femoral and tibial shaft fractures were included. Hole was drilled on medial and lateral sides of bone and passage was created by bone awl. EN, attached to the T-handle, was inserted into the bone. When the nail reached the upper end of fracture site, reduction of fracture was attempted and confirmed under image intensifier. Second nail was introduced from the other side . On fourth post operative day, ambulation with weight bearing was attempted. Results: Twenty two children with femoral and eight with tibial shaft fractures were included. The average healing time for all the fractures was 8.44.8 weeks. Majority (90%) united in less than 3 months. Malunion and delayed union were the commonest complications Reoperation was required in one patient with malunion. None of the patients developed nerve palsy or osteomyelitis Conclusion: Use of flexible intramedullary EN, in the treatment of femoral and tibial shaft fractures in children is feasible with lesser complications